Using dialogue-games in Improving Speaking Ability of participants of advanced level of PIKIH Program - Nurfaizah Sahib (Celebes of Linguistics Journal, 2019)
This research aims at finding out whether or not dialogue-games improves speaking ability significantly better than conventional method and whether or not dialogue-games enhances the interest of participants of advanced level of PIKIH program at UIN Alauddin Makassar in speaking class. This research applied quasi-experimental method. The research data were collected using two kinds of instruments, namely: speaking test and questionnaire. The speaking test was given in the form of interview. The speaking test was to know the students' achievement on speaking ability and the questionnaire was to know the students' interest toward using dialogue-games in speaking class. The findings on speaking ability of the participants were analyzed by using independent sample t-test and the students' interest was analyzed by using descriptive statistic. The findings of the study indicated that the result of post-test was higher than of the pre-test. It means that using dialogue-games and conventional method in teaching English with emphasizes on speaking ability contributed to the students' speaking skill. The study also found that the participants are interested in learning English by using dialogue-games. The study concluded that: (1) Using dialogue-games improved speaking ability of participants of advanced level of PIKIH program at UIN Alauddin Makassar significantly better than conventional method, and (2) the participants were highly interested in learning English by using dialogue-games.